Dynamic routing discovery scheme for high mobility in mobile ad hoc wireless networks - Haider Alani; Maha Abdelhaq; Raed Alsaqour (Institute of Advanced Engineering and Science, 2020)
An innovative technology that is widely used in many applications is the Mobile Ad-hoc Network (MANET). Discovery and maintenance of routes at MANET are important issues. Within MANET, broadcasting is used to discover a path within on-demand routing protocols. Establishing and maintaining a route periodically among the nodes is the challenge that requires the transmitting of control packets across a network. This state leads to the issue of broadcasting storms. Broadcasting control packets increase control packets overhead and decrease network performance. In this paper, we proposed a scheme called AODV-Velocity and Dynamic (AODV-VD) for effective broadcast control packets. The routing protocol for the ad-hoc on-demand distance victor (AODV) is used to implement the proposed AODV-VD scheme. AODV-VD scheme reduces both the excessive route discovery control packets and network overhead. Network simulator version 2.35 (NS2.35) was used to compare the proposed AODV-VD scheme to the AODV routing protocol in terms of end-to-end latency, average throughput, packet transmission ratio and overhead ratio.